Association between psoriasis and inflammatory bowel disease: a Danish nationwide cohort study. (1st September 2016) - Egeberg, A.; Mallbris, L.; Warren, R.B.; Bachelez, H.; Gislason, G.H.; Hansen, P.R.; Skov, L.
Summary: Background: Psoriasis, Crohn disease (CD) and ulcerative colitis (UC) are chronic inflammatory disorders with overlapping genetic architecture. However, data on the frequency and risk of CD and UC in psoriasis are scarce and poorly understood. Objectives: To investigate the association between CD and UC in patients with psoriasis. Methods: All Danish individuals aged ≥ 18 years between 1 January 1997 and 31 December 2012 were linked in nationwide registers. Psoriasis severity was defined in two models: hospital visits and medication. Incidence rates per 10 000 person‐years were calculated, and incidence rate ratios (IRRs) were estimated by Poisson regression. Results: In the total cohort ( n = 5 554 100) there were 75 209 incident cases of psoriasis, 11 309 incident cases of CD and 30 310 incident cases of UC, during follow‐up. The adjusted IRRs (95% confidence intervals) of CD were 1·28 (1·03–1·59), 2·56 (1·87–3·50), 2·85 (1·72–4·73) and 3·42 (2·36–4·95) in patients with mild psoriasis, severe psoriasis (hospital), severe psoriasis (medication) and psoriatic arthritis, respectively. Similarly, the adjusted IRRs of UC were 1·49 (1·32–1·68), 1·56 (1·22–2·00), 1·96 (1·36–2·83) and 2·43 (1·86–3·17), respectively. The 10‐year incidence of CD was 2–5 per 1000 patients and of UC 7–11 per 1000 patients, depending on psoriasis severity and the presence of psoriatic arthritis. Additionally, an increased risk of incident psoriasis was found following CD or UC. Conclusions: We observed a psoriasis‐associated increased risk of CD and UC, which was higher in severe psoriasis, and an increased risk of psoriasis in patients with inflammatory bowel disease. Increased focus on gastrointestinal symptoms in patients with psoriasis may be warranted.